Mepopoidulu: The encounter of the Bible with the Bada tribes in Poso, Indonesia - Fitriani, Kristiana; Sunkudon, Pieter G.O.; Santoso, Joko (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
Mepopoidulu is a significant cultural practice among the Bada people in Poso, Indonesia, reflecting deep social and spiritual values. This study aimed to examine how Mepopoidulu could be theologically contextualised through the approaches of “Faithful Contextualization” and “Global Contextualization.” The research employed a qualitative, descriptive method with contextual hermeneutics to analyse five core components of the tradition. The findings indicated that values such as the sanctity of life, marital holiness, social ethics, gratitude, and restorative justice, embedded in Mepopoidulu, aligned with a Christian worldview. The study contributed to the discourse on indigenous contextual theology by proposing Mepopoidulu as a medium for gospel communication that remains faithful to Scripture while embracing cultural integrity.